2020
DOI: 10.1186/s12913-020-05973-1
|View full text |Cite
|
Sign up to set email alerts
|

Dental visits in Medicaid-enrolled youth with mental illness: an analysis of administrative claims data

Abstract: Background State Medicaid plans across the United States provide dental insurance coverage to millions of young persons with mental illness (MI), including those with attention deficit hyperactivity disorder (ADHD), depression, anxiety, bipolar disorder, and schizophrenia. There are significant oral health challenges associated with MI, and providing dental care to persons with MI while they are young provides a foundation for future oral health. However, little is known about the factors assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
(48 reference statements)
0
0
0
Order By: Relevance
“…It is worth noting that the studies that found this association were conducted in populations of older adults; there is no evidence of this association in populations of adolescents. Depressive symptoms may affect the oral health of individuals by influencing their self-perception and can negatively modifying their behaviors and habits, leading to the development of diseases such as caries and periodontal disease [33].…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that the studies that found this association were conducted in populations of older adults; there is no evidence of this association in populations of adolescents. Depressive symptoms may affect the oral health of individuals by influencing their self-perception and can negatively modifying their behaviors and habits, leading to the development of diseases such as caries and periodontal disease [33].…”
Section: Discussionmentioning
confidence: 99%